Clef ou clé : le traducteur et son lecteur - Abramovici, Serge (2014)
The present study is based on the idea that translation is made from an original text, but is, in itself, multiple and provisional. This is exemplified in Grimm's Tales, following two French translations: Marthe Robert's in 1976 and Armel Guerne's in 1967. Written at different times and for different audiences of readers. According to the author, these translations reveal two distinctive orientations: one which might be characterized as more «reflective», the other more «participative».